HARNESSING INTELLECTUAL CAPITAL FOR INNOVATION: TRENDS, THEORIES, AND FUTURE DIRECTIONS - Tri Wahyudi; Edy Arisondha; Adih Supriadi; Hana Solihat; Aliffa Rhevalina Titiantono (Jurnal Trial Balance, 2026)
This study systematically reviews the role of intellectual capital (IC)—comprising human, structural, and relational capital—as a key driver of innovation. Using Scopus as the primary database and applying a Boolean search strategy, articles published between 2019–2024 were analyzed to identify prevailing trends, theoretical perspectives, and practical implications. Findings reveal that human capital fosters creativity and ideation, structural capital underpins the implementation of innovative solutions, and relational capital enables collaboration and knowledge sharing. The synergy among these components enhances organizational innovation capacity, though gaps remain in standardizing IC measurement frameworks and exploring dynamic interactions. The review highlights the strategic importance of managing IC by investing in employee development, robust knowledge systems, and collaborative networks. It also calls for further research into emerging IC trends and theoretical refinements, offering a comprehensive foundation for advancing the understanding and application of IC in driving sustainable innovation.